The Influence of Interior Element Color on The Activities of Classroom Users in Sps Mutiara Bunda - Seftianingsih, Dina Kristiana; Muhammad Rifai , Dian (Institut Seni Indonesia Surakarta, 2024)
This study investigates the influence of interior element colors on the activities of classroom users at SPS Mutiara Bunda. In the context of early childhood education, color is a critical factor that can impact children's mood, behavior, and learning outcomes. The research aims to explore how the selection of colors in classroom elements—such as walls, furniture, and decorations—affects children's concentration, creativity, and social interaction. The study employs a descriptive qualitative methodology, involving observations, interviews, and document analysis to gain an in-depth understanding of the behavior and responses of children in different classroom settings. The results reveal that certain color schemes significantly enhance children's participation in learning activities, foster positive social interactions, and create an environment conducive to both emotional and cognitive development. The findings provide actionable insights for educators and designers in creating classrooms that better meet the developmental needs of young children.